Bath, city and society in Late Roman Athens - DeForest, Dallas (Journal of Greek Archaeology, 2020)
Baths are ubiquitous in the archaeological record of the Roman Empire – more numerous than any other form of Roman architecture. They are found at virtually every type of settlement, from imperial capitals and mid-sized provincial towns to border fortresses. More so even than theaters, amphitheaters or circuses, baths were an integral part of daily life for urbanites throughout the empire. By the Julio-Claudian era, most could scarcely imagine life without baths, by which time they had become a symbol of Roman identity and civilization. The baths were cultural centers, where debates, educational activities and theological discussions took place; they were places of social intercourse and were used for business transactions; athletes trained in their attached exercise grounds, and subjects of the emperor practiced cult in their halls. Some also served as healing centers, such as the thermal baths at Baiae and Hammat Gader.